Analysis of the contribution of savings in the Credit Union (CU) Tri Tapang Kasih for the welfare of members / community district Semitau Kapuas Hulu 2009-2013 - B01111002, BENY ARFIANTO (Jurnal Pembangunan dan Pemerataan, 2016)
ABSTRACK CU has an important role in supporting the economic improvement Semitau members in the district. CU role in helping improve the welfare of members can be found on the CU loans granted to members in running their business. The data used in this research is data annual members' meeting (RAT) Period 2009-2013 and questionnaire file. The number of questionnaires to get a result that is 50 members. This study discusses the "Contributions savings on CU Tri Tapang Kasih for the welfare of members in the district of Kapuas Hulu Semitau". This research uses qualitative descriptive method and the method of tabulation percentage in order to determine the contribution of CU Tri Tapang kasih in giving loans earning credits towards the development of member businesses in the District Semitau and cause members choose CU Tri Tapang Love as a funding source. These results indicate that the development effort CU Tri Tapang Kasih members has increased profits after obtaining the loan fund productive credit, in other words the member's business is growing rapidly with the living standards of members of a more viable direction prosperous. Keywords: Contributions, Productive Credit, Business Type Members, Welfare.